Effect of Blood Flow Restricted Resistance Exercise and Remote Ischemic Conditioning on Functional Capacity and Myocellular Adaptations in Patients With Heart Failure. (December 2019) - Groennebaek, Thomas; Sieljacks, Peter; Nielsen, Roni; Pryds, Kasper; Jespersen, Nichlas R.; Wang, Jakob; Carlsen, Caroline R.; Schmidt, Michael R.; de Paoli, Frank V.; Miller, Benjamin F.; Vissing, Kristian; Bøtker, Hans Erik
Abstract : Background: Patients with congestive heart failure (CHF) have impaired functional capacity and inferior quality of life. The clinical manifestations are associated with structural and functional impairments in skeletal muscle, emphasizing a need for feasible rehabilitation strategies beyond optimal anticongestive medical treatment. We investigated whether low-load blood flow restricted resistance exercise (BFRRE) or remote ischemic conditioning (RIC) could improve functional capacity and quality of life in patients with CHF and stimulate skeletal muscle myofibrillar and mitochondrial adaptations. Methods: We randomized 36 patients with CHF to BFRRE, RIC, or nontreatment control. BFRRE and RIC were performed 3× per week for 6 weeks. Before and after intervention, muscle biopsies, tests of functional capacity, and quality of life assessments were performed. Deuterium oxide was administered throughout the intervention to measure cumulative RNA and subfraction protein synthesis. Changes in muscle fiber morphology and mitochondrial respiratory function were also assessed. Results: BFRRE improved 6-minute walk test by 39.0 m (CI, 7.0–71.1, P =0.019) compared with control. BFRRE increased maximum isometric strength by 29.7 Nm (CI, 10.8–48.6, P =0.003) compared with control. BFRRE improved quality of life by 5.4 points (CI, −0.04 to 10.9; P =0.052) compared with control. BFRRE increased mitochondrial function by 19.1 pmol/s per milligram (CI, 7.3–30.8; P =0.002) compared with control. RIC did not produce similar changes. Conclusions: Our results demonstrate that BFRRE, but not RIC, improves functional capacity, quality of life, and muscle mitochondrial function. Our findings have clinical implications for rehabilitation of patients with CHF and provide new insights on the myopathy accompanying CHF. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03380663. Abstract : Supplemental Digital Content is available in the text.